Program Literasi Digital dan Etika Media Sosial bagi Pelajar - Hidayat, Asep; Salim, Rodhiyat Fajar; Ilyas; Suherman, Fugiyar (Lembaga Pengabdian kepada Masyarakat Universitas Langlangbuana, 2024)
This Community Service Program aims to improve digital literacy and understanding of social media ethics among high school (SMA) or equivalent students in Buahbatu District, Bandung. With the rapid development of technology, students are increasingly exposed to various risks in the digital world, such as cyberbullying, misinformation, and privacy violations. This program is designed to address two main issues: the lack of awareness and knowledge among students about digital security, and the low understanding of ethics in social media usage. Through an interactive educational approach, the program teaches students how to protect themselves in the digital world, including practicing good security habits and effectively managing privacy settings. Additionally, students are taught to understand and apply ethical principles in their social media interactions, including responsibility in sharing content, respecting copyright, and demonstrating empathy toward others. It is expected that after participating in this program, students will be more proactive in safeguarding their digital security and more ethical in their social media usage, thereby reducing incidents such as cyberbullying and the spread of misinformation. The program also aims to foster a more positive social media culture among students, where interactions are based on mutual respect and shared responsibility.